Bridging Market Orientation to SME Sustainability Performance: Examining Innovation Capabilities Through A Dynamic Capabilities Approach - Satyanegara, Teresa Samantha; Yusup, Adi Kurniawan (SENTRALISASI, 2026)
SMEs are the backbone of Indonesia’s economy, yet they continue to face structural and sustainability challenges. As such, the purpose of this study is to examine how responsive and proactive market orientations impact SMEs’ environmental and financial performance through the mediation of product and process innovation capabilities, and the moderation of market turbulence, grounded in Dynamic Capabilities Theory. This quantitative research used purposive sampling to collect data from 115 SME owners and managers across various industries in Java Island. The data was analyzed using Partial Least Squares Structural Equation Modeling to test the hypotheses. The results showed that a proactive market orientation has a significant impact on financial performance through process innovation capabilities and environmental performance. Contrarily, market turbulence did not moderate the relationship between innovation capabilities and financial performance. This research highlights the importance of proactive market orientation and process innovation capabilities to improve SME sustainability and performance. Based on this study’s findings, SMEs should invest in strengthening their proactive market orientation and process innovation capabilities to achieve sustainability and gain a lasting competitive advantage in the industry.